2013
DOI: 10.1128/cvi.00125-13
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Toxoplasma gondii Infection among Pregnant Women in Northeast Iran

Abstract: bWe report Toxoplasma IgG seroprevalence of 34.4% among 419 pregnant women in Mashhad, northeast Iran. Soil contact, living in rural environment, and level of education were associated with infection. The prevalence did not increase with age, suggesting high infection rate during childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 13 publications
6
14
1
1
Order By: Relevance
“…Although there was no significant difference in T. gondii seropositivity between the Bai groups that feed/do not feed a cat, a significant difference was found in T. gondii seropositivity between Han groups that feed cats and those that do not. Previous studies have indicated that level of education was associated with T. gondii infection [13][14][15]. Similarly, our study showed that T. gondii seroprevalence was significantly different in Han ethnic populations of different educational levels, showing that the proportion of subjects who have college education had lower T. gondii prevalence than others, although there was no significant difference in the Bai ethnic group for different education levels.…”
Section: Discussionsupporting
confidence: 70%
“…Although there was no significant difference in T. gondii seropositivity between the Bai groups that feed/do not feed a cat, a significant difference was found in T. gondii seropositivity between Han groups that feed cats and those that do not. Previous studies have indicated that level of education was associated with T. gondii infection [13][14][15]. Similarly, our study showed that T. gondii seroprevalence was significantly different in Han ethnic populations of different educational levels, showing that the proportion of subjects who have college education had lower T. gondii prevalence than others, although there was no significant difference in the Bai ethnic group for different education levels.…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, despite the non-statistical significant association between T.gondii infection and the residential place, comparatively higher seroprevalence was observed in rural pregnant women than urban dwellers in parallel with previous report. 48,45 This is due to the presence of domestic animals and favorable environmental conditions for survival and sporulation of T.gondii oocysts. In contrast previous studies showed high seropositivity of T.gondii infection in urban pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although, it has previously been demonstrated that the educational level is an important risk factor for the occurrence of T. gondii infection, no association was detected in this study. In general, people with a higher educational level have more knowledge about this infection and the methods of its prevention (11) . As a similar lack of association was observed regarding the origin of samples (i.e., rural or urban areas), it is probable that the number of samples analyzed was small and lacked power to detect differences in infection rates across these parameters.…”
Section: Rev Soc Bras Medmentioning
confidence: 99%
“…In general, the lowest prevalence has been reported in North America, whereas in Latin America, and particularly in countries such as Brazil, Colombia, and Cuba the prevalence of infection might reach 70% (10) (11) . The wide prevalence range is due to the different risk factors, which might infl uence the likelihood of infection by T. gondii in a given population (e.g., ingestion of undercooked meat, unpasteurized milk, or educational level) (5) (12) .…”
mentioning
confidence: 94%